2023
DOI: 10.2147/ijn.s393890
|View full text |Cite
|
Sign up to set email alerts
|

PLCL/PCL Dressings with Platelet Lysate and Growth Factors Embedded in Fibrin for Chronic Wound Regeneration

Abstract: Introduction The formation of diabetic ulcers (DU) is a common complication for diabetic patients resulting in serious chronic wounds. There is therefore, an urgent need for complex treatment of this problem. This study examines a bioactive wound dressing of a biodegradable electrospun nanofibrous blend of poly(L-lactide-co-ε-caprolactone) and poly(ε-caprolactone) (PLCL/PCL) covered by a thin fibrin layer for sustained delivery of bioactive molecules. Methods Electrospu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The advantages of the coating method include simple operation, ease of achieving a uniform drug distribution on the scaffold surface, the ability to load multiple drugs for combined therapeutic effects, and the ability to regulate the drug loading and release rate by adjusting factors such as the drug solution concentration and coating method [ 194 ]. However, due to the weak binding between the drug and the scaffold in the coating method, the drug release rate may be too fast, which is not conducive to achieving sustained and controlled release [ 195 ]. It is worth mentioning that the physisorption method is more suitable for small molecules, where the drug is attached to the scaffold by van der Waals forces, whereas the encapsulation method is more suitable for large molecules (e.g., proteins), which mainly involves trapping the drug molecules within the pores of the material [ 196 , 197 , 198 ].…”
Section: Nanofiber Scaffold Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of the coating method include simple operation, ease of achieving a uniform drug distribution on the scaffold surface, the ability to load multiple drugs for combined therapeutic effects, and the ability to regulate the drug loading and release rate by adjusting factors such as the drug solution concentration and coating method [ 194 ]. However, due to the weak binding between the drug and the scaffold in the coating method, the drug release rate may be too fast, which is not conducive to achieving sustained and controlled release [ 195 ]. It is worth mentioning that the physisorption method is more suitable for small molecules, where the drug is attached to the scaffold by van der Waals forces, whereas the encapsulation method is more suitable for large molecules (e.g., proteins), which mainly involves trapping the drug molecules within the pores of the material [ 196 , 197 , 198 ].…”
Section: Nanofiber Scaffold Technologymentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) is the most common growth factor incorporated into nanofiber scaffolds for the promotion of angiogenesis [ 185 ]. Other growth factors, such as fibroblast growth factor (FGF) [ 195 ], platelet-derived growth factor (PDGF) [ 225 ], and transforming growth factor-β (TGF-β) [ 226 ], can also synergistically promote angiogenesis. Some cytokines, such as monocyte chemoattractant protein-1 (MCP-1) and interleukin-8 (IL-8) [ 227 , 228 ], can induce endothelial cell migration and proliferation, thereby promoting angiogenesis.…”
Section: Application Of Nanofibrous Scaffolds In Wound Healingmentioning
confidence: 99%
“…In the wound healing model, the NFM showed a 96.39 ± 0.66% wound healing rate, and the promoting effect of growth factors on wound healing was demonstrated. Taborska et al [122] used poly(L-lactide-co-ε-caprolactone)/PCL nanofibers as a matrix containing human platelet lysates (hPL), and the fibrin network of VEGF and FGF as a coating to prepare a composite wound dressing. The results showed that the fibrin network was a good receptacle for bioactive molecules, and the sustained release of growth factors and hPL from the coating significantly increased the survival rate of human saphenous vein endothelial cells in collagen wound models.…”
Section: Growth Factorsmentioning
confidence: 99%